Parenting styles and social media addiction among adolescents in the Peruvian jungle - Sandoval-Correa, Daniela (2024)
Objective. To evaluate the relationship between parenting styles and addiction to social media among students in state educational institutions in the Peruvian jungle, 2022. Methodology. The research had a quantitative, correlational, nonexperimental, and cross-sectional approach. The population consisted of 300 students, while the sample was formed by 250 students, included through intentional non-probabilistic sampling. Steinberg's parenting styles scale and the Social Media Addiction Questionnaire (ARS-6) were used. The Spearman's rho statistical test and the Fisher test were also employed. Results. When verifying the relationship of parenting styles, in the commitment dimension,a rho coefcient of -0.112; p = 0.07 was observed, indicating no relationship in the behavioral control dimension (rho = -0.103), while a significant relationship was evidenced in the autonomy dimension (rho = 0.148, p = 0.020). Conclusion. It was found that parenting styles in the commitment and autonomy dimensions were not related to social media addiction; however, the autonomy dimension did have a relationship with social media addiction among students in state educational institutions in the Peruvian jungle, 2022.